Effect of Qualities of Service and Funding Product on Brand Image And Loyalty of Sharia Bank Customers in Bogor - Afiatin Dewi; Mukhamad Najib; Irfan Syauqi Beik (School of Business, IPB University (SB-IPB), 2018)
This research objective is to determine the correlation between service and product qualities and customer’s loyalty and brand image of sharia banking in Indonesia. This is a descriptive research whose objects included Bank Muamalat, Bank BNI Syariah, Bank Permata Syariah, and Bank BTN Syariah located in Bogor City. This research used Structural Equation Model (SEM) method as a research analysis tool with 200 customers as the respondents. The proper Sharia Banking’s value is not only reflected in terms of service but also in developing products that can compete with conventional banks. The features in the products have provided easiness in transactions for customers and are free from riba. Based on the test, service and product qualities simultaneously have positive effects on brand image, and brand image positively affects the loyalty of sharia banking customers.Keywords: sharia banking, service quality, product quality, brand image, and customer loyalty